Chemokines and inflammation: a critical assessment of therapeutic targets - Greaves, David (Henry Stewart Talks, 2009)
Introduction to chemokine biology, Chemokine receptors, Decoy chemokine receptors, Chemokine evolution, Chemokine function, Acute and chronic inflammation, Chronic inflammatory diseases, Chemokines and leukocyte recruitment, Chemokine function in atherosclerosis, CCL2 acting via CCR2, CCL3, 4, 5 acting via CCR1 and CCR5, CXCL9, 10, 11 acting via CXCR3, CX3CL1 acting via CX3CR1, Targeting chemokines in atherosclerosis and other forms of inflammation, Neutralising antibodies, Small molecule inhibitors, Mutant chemokines, Broad-spectrum chemokine blockade